Implementation of Immigration Supervision Refugees at Community House In Under Control Supervision of Immigration Detention House Jakarta - Asto Yudho Kartiko; Jennifer Cecilia Telaumbanua; Tsaltsa Syah Putri (Journal of Law and Border Protection, 2019)
Indonesia is one of the countries that has not ratified the 1951 Convention on refugees but that does not prohibit refugees from coming and getting protection in Indonesia because based on the prevailing constitution, Indonesia has the responsibility to handle refugees and carry out immigration control over them. With the existence of Government Regulation Number 125 of 2016 concerning Handling of Refugees from Abroad, immigration plays a role in collecting data, placing, monitoring, and returning refugees to their home countries or third countries. Supervision is an important action taken in dealing with refugees while in Indonesia. Refugees who have received approval from UNHCR and have special needs will be placed in the Community House. The formulation of the problem in this study is how to implement immigration control for refugees in the Jakarta Community House and what obstacles are found in conducting surveillance. The purpose of this research is to find out how the implementation of immigration control carried out on refugees in Community House Jakarta. The research method used is normative empiris, using primary and secondary data, studying and evaluating phenomena about refugees and legal norms related to refugees and immigration control obtained from literature and law, then analyzed to get conclusions. So it can be explained that the implementation of immigration control of refugees at the Jakarta Community House is carried out by means of attendance and data collection on refugee identification cards and stamps and signatures of Jakarta Rudenim officers. The obstacle to monitoring at the Community House is that there is still conflict between the refugees and the refugee's poor health condition.